An Architecture for Creating Slices to Experiment on Wireless Networks. - Valera-Muros, Bárbara; Panizo-Jaime, Laura; Rios, Álvaro; Merino-Gómez, Pedro (Springer Nature, 2020)
Researchers in mobile technologies and services are currently requesting testbeds to validate their proposals in a realistic large-scale and controlled environment. Such demands are some times satisfied with private ad-hoc deployments in a given area of coverage. However, given national regulations related to the use of the spectrum and the cost of deployments, these solutions are not feasible for most researchers. In this paper, we introduce the architecture of the research infrastructure developed in the EuWireless project. EuWireless’ objective is to provide private networks that can be dynamically created as slices with different levels of configuration and control, as a cost-effective way to access large-scale testbeds with a licensed spectrum even in different countries. The paper focuses on the architecture of the Point of Presence, the key element in the EuWireless project, and how it will work in practice. We also present a proof of concept implementation that satisfies some of the design objectives and demonstrates the feasibility of the proposal.
Keywords: Redes de ordenadores - Arquitecturas; Sistemas de comunicaciones inalámbricos; 5G; Private network; Slice; Research infrastructure